Assessment of Climate Change Awareness In Urban Versus Rural Populations: A Comparative Study - De Jesus, Dennis A. (the International Journal of Education, Theology, and Humanities, 2024)
In this study, the researchers explore and contrast climate change awareness in the urban and rural populations by looking into their knowledge, perception, and engagement. Using a structured survey instrument, data were collected from 500 respondents irrespective of age gender location and with equal distribution. Results indicate awareness differences, with urban respondents being more informed on the causes of climate change than the rural respondents who were more aware of the effects in their immediate environment. From the results, it can be concluded that any attempts in marketing climate change strategies needs to be targeted to the respective areas of the two groups studied. This emphasizes how critical educational and outreach programs geared towards climate change issues in specific regions are.